Abundance of whitegrubs (Coleoptera: Melolonthidae) in two colombian agroecosystems - PARDO-LOCARNO, LUIS CARLOS; MONTOYA-LERMA, JAMES; SCHOONHOVEN, AART (Revista Colombiana de Entomología, 2003)
The composition and variation in the frequency of soil pests, especially the whitegrub (larvae of Coleoptera, family Melolonthidae) were studied in Caldono and Buenos Aires. These are two agriculturaL locations in the Department of Cauca (elevation ranges from 1.400-1.500 meters above sea level. temperature of 21.5ºC and precipitation averaging 2.192 mm/year). This study showed that the whitegrub complex was composed of several species, in different stages of development. Samples were taken to determine the number and influence of root-feeding whitegrubs on plant damage. This was done in four different agro-ecologies: cassava, pasture, coffee under the shade, and forest fields. Each plot had an area half an hectare and samples were taken every 15 days. with 12 samples dates, from which four were used for the statistical analysis. A total of 12.512 adults and 10.261 larvae were collected, which represented 32 species within the family Melolonthidae. The statistical analysis of the selected data revealed significant differences in a number of individuals from localities (F =248,83; p=0.0), between samples (F=20,27; p=6,02) and between the four types of habitat when the two localities were combined for analysis (F=34,43; p=4, 7). In conclusion, there were similarities in the structure of the complex of whitegrubs in Caldono and Buenos Aires (Cauca), however, when an abundance of whitegrubs was analyzed in detail, statistical differences were noted between the four ecologies selected for the study, which are explained by variations in climate and soils between localities. The data obtained allow us to conclude that the damage caused by whitegrubs is more severe in Caldono than in Buenos Aires.